Reorganizing stroke and neurological intensive care during the COVID-19 pandemic in Germany - Kämpfer, Niklas Alexander; Naldi, Andrea; Bragazzi, Nicola Luigi; Fassbender, Klaus; Lesmeister, Martin; Lochner, Piergiorgio (Acta Biomedica Atenei Parmensis, 2021)
The outbreak of coronavirus disease 19 (COVID-19) has dramatically imposed healthcare systems to reorganize their departments, including neurological wards. We aimed to describe the rearrangements made by stroke units (SU) and neurological intensive care units (ICU) in several German community and university hospitals facing the pandemic.This cross-sectional, survey-based, nationwide study collected data of 15 university and 4 community hospitals in Germany, being part of IGNITE Study Group, from April 1 to April 6, 2020. The rearrangements and implementation of safety measures in SUs, intermediate care units (IMC), and neurological ICUs were compared.84.2% of hospitals implemented a separated area for patients awaiting their COVID-19 test results and 94.7% had a dedicated zone for their management. Outpatient treatment was reduced in 63.2% and even suspended in 36.8% of the hospitals. A global reduction of bed capacity was observed. Hospitals reported compromised stroke treatment (52.6%) and reduction of thrombolysis and thrombectomy rates (36.8%). All hospitals proposed special training for COVID-19 management, recurrent meetings and all undertook measures improving safety for healthcare workers.In an unprecedented global healthcare crisis, knowledge of the initial reorganization and response of German hospitals to COVID-19 may help finding effective strategies to face the ongoing pandemic.